2017
DOI: 10.1016/j.crvi.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Les microRNA comme biomarqueurs : quelles perspectives ?

Abstract: MicroRNAs are nucleic acids of about twenty nucleotides that regulate about a third of the genome at the post-transcriptional level. Thanks to their different forms of transport, microRNAs are stable and can be detected in biological fluids such as blood, urine, cerebrospinal fluid, or saliva. In addition, the profile of circulating microRNAs is a specific part of the cells in which it is secreted and is modified according to the physiological or pathological conditions of these cells. MicroRNAs therefore appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 120 publications
0
19
0
Order By: Relevance
“…MicroRNAs, as a class of noncoding small RNA molecules, can regulate gene expression at the posttranscriptional level by binding to the 3' UTR of target mRNAs [ 20 , 21 ]. Currently, it is generally believed that miRNAs are not only connected with the physiological processes of proliferation, apoptosis, proliferation, and embryonic development but can also be involved in cancer progression by acting as a carcinogen or tumor suppressor gene [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs, as a class of noncoding small RNA molecules, can regulate gene expression at the posttranscriptional level by binding to the 3' UTR of target mRNAs [ 20 , 21 ]. Currently, it is generally believed that miRNAs are not only connected with the physiological processes of proliferation, apoptosis, proliferation, and embryonic development but can also be involved in cancer progression by acting as a carcinogen or tumor suppressor gene [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs can be used as prognostic markers for malignant tumors, while other miRNA molecules are potential targets for cancer treatment [29]. Considering the expression of miRNAs almost affects all stages of malignant tumors: occurrence, development, metastasis and drug resistance [30] and it is relatively stable and can be detected in a variety of biological uids, such as blood, urine, cerebrospinal uid and saliva [31], miRNAs may become more effective biomarkers in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have reported that changes of miRNAs observed in certain biological fluids correlate with various pathological conditions suggesting that circulating miRNAs might be useful and informative biomarkers to reflect the pathological status of the body (Valentino et al, 2017 ; Wang, 2017 ; Zendjabil et al, 2017 ; Zhao et al, 2017 ). Evidence has emerged that miRNAs in blood or cerebrospinal fluid may serve as potential biomarkers of brain injury (Weber et al, 2010 ; Kulstein et al, 2016 ; Martinez and Peplow, 2016 ; Sirker et al, 2016 ; Wang, 2017 ).…”
Section: Microrna and Epilepsymentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides that have little or no protein-coding capacity, and have drawn intense research efforts recently (Schaukowitch and Kim, 2014 ). While lncRNAs were at first considered transcriptional noises, recent studies have demonstrated that they play essential roles in biological pathways, including X inactivation, imprinting, development, and differentiation (Danis et al, 2016 ; Valentino et al, 2017 ; Zendjabil et al, 2017 ). lncRNAs can regulate many processes in mammalian and gene expression through a diversity of mechanisms and at different levels, but the available research tools are still insufficient.…”
Section: Long Non-coding Rnamentioning
confidence: 99%